Sociopolitical Analysis of The Escalation of The Islamic Defenders Front (FPI) Movement During The Reign of Basuki Tjahaja Purnama (Ahok) in DKI Jakarta 2014-2017 - Fachriel Haykal Maulana; Taufik Nurohman; Faisal Fadilla Noorikhsan (Epistemik Press, 2022)
This study analyze how social conditions during the reign of Basuki Tjahaja Purnama (Ahok) affected the escalation of the Islamic community organization Front Pembela Islam (FPI) movement and built the reality of socio-political conflicts that occurred in DKI Jakarta from 2014 to 2017. The method used in this research is a qualitative research method using a case study approach. The case study approach was used to analyze how the process of forming the escalation of the Islamic community organization movement of Front Pembela Islam (FPI) against socio-political conditions during Ahok's reign in DKI Jakarta from 2014 to 2017. Using theories related to the concept of Political Opportunity, New Social Movements, and Identity Theory becomes an analytical knife to explain questions that have been formulated academically and, of course, produce an answer from the results of the analysis. From the results of the research, the Islamic Mass Organization of Front Pembela Islam (FPI) was one of the Organizations that experienced an escalation of the movement based on various conflicts that occurred both before, during his time in office, and also after Ahok served as governor of DKI Jakarta. FPI is present as a hard-pressure group for Ahok's refusal to become Governor. FPI became one of the organizations considered very active and aggressive in carrying out a series of protests against Ahok's rejection.